World records in finswimming sport: growth profiling analysis - Moskovchenko, O. N.; Tolstopyatov, I. A.; Redi, E. V.; Ivanitsky, V. V.; Zakharova, L. V. (Theory and Practice of Physical Culture, 2019)
The finswimming discipline has been cultivated since 1969 and still remains one of the most popular and spectacular disciplines of underwater sports recognized by the International Olympic Committee (IOC). Championships of Russia, Europe, world championships as well as Russian and World Cups are being held in this discipline with records of senior and junior finswimmers being registered. However, it should be noted that the analysis of the dynamics of world records is beyond the scope of attention of trainers and researchers, as confirmed by other researchers. Subject to the study was the world record statistics in the 100/ 200/ 400/ 800m surface finswimming; 400/ 800m women`s underwater finswimming ;100/ 200/ 400/ 800/ 1500m surface finswimming; and 100/ 400m men`s underwater finswimming events, with the top-ten results in the European and World Championships mined for analysis.